2022
DOI: 10.3389/fresc.2022.891571
|View full text |Cite
|
Sign up to set email alerts
|

Health professional perspectives on translation of cultural safety concepts into practice: A scoping study

Abstract: People from unique and diverse populations, (i.e., social groupings excluded by the dominant majority by, for example, ethnicity, gender, age, sexual orientation, disability or even rurality), experience dissimilar health outcomes. Members of such populations who have long-term health conditions experience further health disparities through inefficient management and treatment. This remains a significant hindrance to achieving equity in health outcomes. Being responsive and acting upon the cultural needs of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Creating a space that is welcoming for all and that is considered culturally safe by Indigenous peoples (in NZ, that is Māori) is suggested to assist in addressing health disparities [45]. In this study, the MSE space was identified as unwelcoming for Māori users and potentially others who struggled with the booking and payment systems, as well as accessing the room itself.…”
Section: Discussionmentioning
confidence: 93%
“…Creating a space that is welcoming for all and that is considered culturally safe by Indigenous peoples (in NZ, that is Māori) is suggested to assist in addressing health disparities [45]. In this study, the MSE space was identified as unwelcoming for Māori users and potentially others who struggled with the booking and payment systems, as well as accessing the room itself.…”
Section: Discussionmentioning
confidence: 93%
“…Why far less Māori, and no Pacific Island, students participated in our study is not known. However, one reason could be that self-management of health is of itself a cultural artefact, largely driven by white Western, neoliberal philosophies (Wilson et al, 2022), and for many cultural groups that value collectivism, such as Māori and Pacific Island cultures, "self"-management may be incongruent with their ways of being. This concept suggests that culture not only possibly impacts on how we teach SSM but that the concept in itself needs further in-depth exploration and understanding in a country such as New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Many would contend that the philosophy of focusing on the ‘self’ is problematic in and of itself (Ould Brahim 2019 ). Wilson, Wilkinson and Tikao ( 2022 ) argue that:…”
Section: Challenging the Concept Of ‘Self-management’mentioning
confidence: 99%
“…Conversely, with collectivism, where the groups people belong to, such as family and community, are highly valued, the ‘self’ becomes less prominent (Realo 2003 ) and thereby incongruent with the concept of ‘self-management’ of health. Such debates are evolving in nations where the ideologies of collectivism stand out (Basurrah, Al-Haj Baddar & Di Blasi 2022 ; Wilson et al 2022 ). So, what of the African viewpoint?…”
Section: Challenging the Concept Of ‘Self-management’mentioning
confidence: 99%